Peasant Listening, Listening to Peasants: Miscommunication and Ventriloquism in Nekrasov's "Komu na Rusi zhit′ khorosho". Issue 4 (1st September 2013) - OGDEN, J. ALEXANDER
Abstract : Nikolai Nekrasov's fascination with peasant speech culminated in his book‐length narrative poem "Komu na Rusi zhit' khorosho" (1860s–1870s). Nekrasov's words seem almost to merge with a larger world of folk production—an apparent convergence that glosses over a number of questions about the distance between the poem's actual author and audience, on the one hand, and its narrator and implied audience, on the other. The work as a whole provides a particularly interesting case study for ideas of communication between peasants and non‐peasants, since listening to and telling stories lie at the heart of "Komu na Rusi zhit' khorosho." The times within the work when communication breaks down are particularly noticeable; Nekrasov often uses the misunderstandings or deceptions that arise to comment indirectly on the characters or situations involved. The issues raised by the kinds of miscommunication highlighted within the poem are ignored, however, on a metapoetic level. In addition to examining both examples of miscommunication within "Komu na Rusi zhit' khorosho" and the communicative situation between Nekrasov and his audience, this article places Nekrasov's work in two larger contexts: the interactions between peasants and nonpeasants in Reform‐era Russian, which were dependent on listening and were often fraught with misunderstandings, and the pan‐European romantic insistence on the role folk language should play in revitalizing culture. The article also introduces a recent elaboration of speech act theory to clarify the ventriloquy Nekrasov engages in to "channel" a peasant voice.